Le tourisme sexuel vu du Sahara marocain : une économie de razzia ? - Corinne Cauvin Verner (L’Année du Maghreb)
Trekking itineraries and camping trips on the edge of the Sahara desert in Morocco are frequently the scene of sexual exchanges between Western female tourists and their guides, who are members of settled Saharan Bedouin tribes. With no price tag, or even payment requested, these interactions seem to be the starting point of more or less perennial liaisons. A monographic study within the tribal group reveals complex transactional logics which defeat all theories of any type of prostitution. Emancipation rather than transgression, a raiding economy rather than prostitution, an aesthetics of fantasia rather than debauchery, the seduction and capitalization of foreign women is part of a common economic and lineage rationality around the reaffirmation of a Bedouin ethos.